Desenvolvimento e caracterização de composições polipropileno/cargas retardantes de chama - Trombini, Rejane Cristina (2004)
The main objective of this study was to develop and characterize polypropylene modified with flame retardant fillers. Two flame retardant fillers (Aluminum Hydroxide and Magnesium Hydroxide) were incorporated into four distinct types of polypropylene, two of which were homopolymers and two copolymers. The contents of the flame retardant fillers were 40 and 60%, in mass. The composites were prepared using two co-rotating double screw extruders, one a bench scale device and the other of considerably larger dimensions. The test specimens were then injection processed, after which the composites thermal, mechanical, thermomechanical and flammability performance were evaluated. An analysis was made of the thermogravimetric results to identify the possible occurrence of water loss during the composite s processing. The flame retardant fillers were found to improve the composite s flammability behavior, albeit with a concomitant decrease in their mechanical properties, most notably a drop in the material s impact strength. The best physical and mechanical properties and the lowest flammability were obtained with polymer-flame retardant filler composites whose polymeric matrix was composed of propylene-ethylene copolymer with the highest ethylene content. A study was also made of the properties of polypropylene and organic clay nanocomposites, from which a type of polypropylene most closely resembling the ones previously studied was chosen to serve as a standard against which to compare the properties obtained for the polypropylenes modified with traditional flame retardant fillers. Under the conditions utilized in this study, the nanocomposites displayed an adequate physical and mechanical behavior, but the evaluations revealed that no satisfactory increase in resistance to flammability was achieved.